2021
DOI: 10.1186/s13287-021-02407-5
|View full text |Cite
|
Sign up to set email alerts
|

hPMSCs inhibit the expression of PD-1 in CD4+IL-10+ T cells and mitigate liver damage in a GVHD mouse model by regulating the crosstalk between Nrf2 and NF-κB signaling pathway

Abstract: Background The activation of T cells and imbalanced redox metabolism enhances the development of graft-versus-host disease (GVHD). Human placenta-derived mesenchymal stromal cells (hPMSCs) can improve GVHD through regulating T cell responses. However, whether hPMSCs balance the redox metabolism of CD4+IL-10+ T cells and liver tissue and alleviate GVHD remains unclear. This study aimed to investigate the effect of hPMSC-mediated treatment of GVHD associated with CD4+IL-10+ T cell generation via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…PMSCs adhered to cell culture plates after 3 days of culture, and the third passage of PMSCs showed fibroblastic morphology (Figure S1(a) ). The expression of surface markers CD44, CD73, CD90, and CD105 was positive, while the expression of surface markers CD31, CD34, and CD45 was negative (Figure S1(b) ), which was consistent with previous reports [ 6 , 51 , 52 ]. PMSCs also successfully formed calcified bone nodules, lipid droplets, and cartilage in the osteogenic, adipogenic, and chondrogenic differentiation assays (Figure S1(c) ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…PMSCs adhered to cell culture plates after 3 days of culture, and the third passage of PMSCs showed fibroblastic morphology (Figure S1(a) ). The expression of surface markers CD44, CD73, CD90, and CD105 was positive, while the expression of surface markers CD31, CD34, and CD45 was negative (Figure S1(b) ), which was consistent with previous reports [ 6 , 51 , 52 ]. PMSCs also successfully formed calcified bone nodules, lipid droplets, and cartilage in the osteogenic, adipogenic, and chondrogenic differentiation assays (Figure S1(c) ).…”
Section: Resultssupporting
confidence: 92%
“…PMSCs were incubated with PBS or fluorescein-labeled antibodies for 30 min. The tested antibodies included CD90, CD 105, CD73, CD44, CD34, CD31, and CD45 (Biolegend, USA) as previously reported [ 6 , 51 , 52 ]. Isotype-identical antibodies were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consents were also obtained. Based on previously described methods [ 19 , 27 , 28 ], PMSCs were isolated from term placentas collected from healthy donors who had gone through elective cesarean sections due to the breech position or previous history of cesarean section. The placental tissue was taken from the center area around the umbilical cord attachment site and was gently washed with preheated phosphate-buffered saline (PBS, pH 7.2 ± 0.1, Genome Sciences), minced into 1mm 3 pieces, and digested with gentle shaking in 0.1 mg/mL type I collagenase (Gibco) for 60 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell suspensions were incubated with PBS or fluorescein-labeled antibodies for 30 min. The tested antibodies included CD73, CD90, CD105, CD31, CD34, CD45, and HLA-DR (BD Biosciences, USA) as previously reported [ 19 , 27 , 28 ]. Isotype-identical antibodies were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Yoo et al showed that MSCs suppress T cells by inhibiting CD25 translation through the LKB1-AMPK-mTOR pathway [ 14 ]. Furthermore, Zhang et al found that human placenta (hP)-MSCs could inhibit PD-1 expression in CD4 + IL-10 + T cells and alleviate liver injury in a graft versus host disease mouse model by regulating the crosstalk between Nrf2 and NF-κB signaling pathways [ 15 ]. Regulatory T cells (Tregs) play a crucial role in inhibiting immune cell-mediated hepatocyte injury during fulminant hepatitis [ 40 ].…”
Section: Mechanism Of Mscs In Treating Liver Diseasementioning
confidence: 99%